Difficulties in Utilizing Digitally-Mediated Authentic English Teaching Materials from The Perspective of Madrasah Teachers - Putera, Lalu Jaswadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
In the 21st century, digital literacy has become a fundamental competency for teachers, particularly in English language teaching. However, many madrasah teachers continue to face significant difficulties in utilizing and integrating digital tools and resources into their classroom practices. This study aims to investigate the challenges or difficulties encountered by rural and semi-urban madrasah English teachers in utilizing digitally-mediated authentic teaching materials. Using a mixed-methods approach, data were collected from 37 participants through questionnaires and interviews. The findings revealed three main categories of difficulties: technical barriers, competency gaps, and contextual constraints. Technically, while 70% of teachers reported that students have access to digital devices, only 25% had stable internet access, and over 72% lacked essential teaching tools (APE: Alat Peraga Edukatif). In terms of competency, only 18.9% felt confident using platforms such as Canva, interactive LiveWorksheets, or Google Forms, and just 5.4% were confident in designing tasks based on local resources. Contextually, 86.4% lacked access to information about seminars or training, and 67.6% noted that professional development activities are rarely available in madrasahs (Islamic schools). The study concludes that these challenges require targeted interventions such as digital literacy training adapted to low-resource contexts, collaborative forums for material development, and broader access to professional development platforms such as the National Geographic Learning webinars and many others.